The Decision Criteria for the International Entry Mode for Badan Pengelola Keuangan Haji: an Application of Analytical Hierarchy Process - Medina Azzahra Hadar; Yos Sunitiyoso (Green Publisher Indonesia, 2025)
Badan Pengelola Keuangan Haji (BPKH), a government agency mandated to manage hajj funds, is authorized to invest abroad under Law No. 34 of 2014. In 2023, BPKH established its first subsidiary in Saudi Arabia through Sole Ownership (Greenfield) as its chosen international entry mode. However, the organization currently lacks a formal framework for selecting the optimal mode. This study aims to determine and prioritize decision criteria for BPKH’s international entry mode selection and to develop a decision-making model to support future investments. Using the Analytic Hierarchy Process (AHP), the study systematically evaluates qualitative and quantitative criteria derived from the Eclectic Paradigm framework and expert interviews with seven key BPKH decision-makers. Expert pairwise comparisons indicate that Location Advantage is the most influential criterion (0.519). Among sub-criteria, Organizational Capability (0.175), Part of the Hajj Ecosystem (0.170), and Market Potential (0.154) rank highest in influence. The analysis of four alternative entry modes shows the following ranking: (1) Sole Ownership (Acquisition) with a score of 68.82; (2) Majority Joint Venture (58.06); (3) Sole Ownership (Greenfield) (57.75); and (4) Minority Joint Venture (52.94). The findings provide a structured model enabling BPKH to make better-informed and accountable international expansion decisions aligned with its mission to optimize hajj fund management for the benefit of Indonesian pilgrims.